Industrial and innovation policy as drivers of change - David Bailey; Lisa De Propris; Jürgen Janger (WWWforEurope, 2015)
The Europe's 2020 Strategy clearly outlines the ambition for EU member states to pursue a smart, sustainable and inclusive growth: this means designing a the strategy that aims at achieving a socio-ecological transition by fostering economic growth as well as social development (e.g. with respect to employment, gender or cultural aspects) whilst also pushing for Europe's green shift. To deliver the EU 2020 strategy a new definition of competitiveness needs to be considered. Aiginger et al. (2013) propose defining competitiveness as the ability to deliver beyond-GDP goals. Competitiveness should be based on capabilities like skills, innovation, institutions, an empowering social system, and ecological ambitions. Outcomes should be defined by the achievement of ecological, social and economic goals. The new industrial policy for Europe will be underpinned by four game changers: (a) From GDP to beyond-GDP (b) A new definition of competitiveness (c) the green shift and (d) high road growth. Aiginger (2015) proposes to define industrial policy as economic policy to promote the competitiveness of a country or region, where competitiveness is defined as the ability to deliver the beyond-GDP goals. This means an industrial policy that shows leadership towards Europe's green shift; this means not only pursuing - for instance - energy efficiency and applications of the circular economy, but that supports the conversion of the economy into a green-intensive economy with the creation of new sectors, new processes, new products and the emergence of "green gazelles", that can deliver growth and jobs through ecological innovations. Industrial policy should foster the long-run transition, not decelerate structural change. This is a demanding challenge, given vested interests and the traditional role of governments to preserve the status quo and national champions. Refocusing on the economy's industrial base is a necessity to anchor long term socio-economic prosperity, particularly after the experience of bubbles in financial and real estate markets. A new industrial policy for Europe should therefore pursue a balanced economy and support the transition of traditional, narrowly defined manufacturing sectors to an advanced and distributed manufacturing sector able of greater value creation, innovation and creativity.
Keywords: L5; L52; L53; L59; 330; Industrial innovation; Industrial policy; Innovation policy; Intangible assets; New technologies; Patents; Post-industrialisation; Research; SMEs; Sustainable growth; Wirtschaftswachstum; Soziale Integration; Technologiepolitik; Europa